ENILAIAN STATUS GIZI UNTUK MENCEGAH MASALAH GIZI DAN KESEHATAN REPRODUKSI WANITA USIA SUBUR (WUS) DI EXECUTIVE TAHFIZH CENTRE YOGYAKARTA - Elly Naila Fauziah (Permata Indonesia, 2023)
Background: Energy and nutritional needs are influenced by reproductive age, activity level, andnutritional status. (Marmi, 2013) Executive Tahfizh Center (ETC) Yogyakarta is an educational institutionfor quarantine memorizing the Koran and all of its participants live in one place. The subject of thiscommunity service is all female students (19 people) aged 15-36 years. This nutritional statusassessment is important, considering the high productivity of students in implementing this quarantineprogram and to prevent nutritional and reproductive health problems for Women of Reproductive Age(WUS). Methods of implementation: Nutrition counseling on reproductive health, anthropometricexaminations in the form of measuring body weight (BB) and height (TB) to obtain a measure ofnutritional status according to Body Mass Index (BMI), as well as age observation and measurement ofupper arm circumference (LILA) to obtain measure of nutritional status according to LILA. Results anddiscussion: The results of measuring nutritional status according to the BMI classification were 16normal people, 2 people who were severely obese, and 1 person who was mildly thin. Nutritional statusaccording to LILA classification, 15 people with good nutrition, 2 people with obesity, 1 person withoverweight, and 1 person with severe nutrition. Conclusion: Community service activities throughcounseling and nutritional status assessment can increase knowledge and provide an overview ofstudents' nutritional status. Counseling and evaluating nutritional status needs to be carried out regularlyto prevent nutritional and reproductive health problems, so as to support student productivity duringquarantine.